Platelet-activating factor synthesis and receptor-mediated signaling are downregulated in ovine newborn lungs: relevance in postnatal pulmonary adaptation and persistent pulmonary hypertension of the newborn. (22nd July 2013) - Renteria, L. S.; Cruz, E.; Ibe, B. O.
Abstract : Platelet-activating factor (PAF) is a phospholipid with a wide range of biological activities. We studied PAF metabolism and PAF receptor (PAFR) signaling in perinatal ovine lungs to understand PAF's role in transition of the perinatal pulmonary hemodynamics and pathophysiology of persistent pulmonary hypertension of the newborn. We hypothesized that downregulation of PAF synthesis with upregulation of PAF catabolism by acetylhydrolase (PAF-Ah) in the newborn lung is needed for fetus-to-newborn pulmonary adaptation. Studies were conducted on fetal and newborn lamb pulmonary arteries (PA), veins (PV) and smooth muscle cells (SMC). PAF metabolism, PAFR binding and cell proliferation were studied by cell culture; gene expression was studied by qPCR. Fetal lungs synthesized 60% more PAF than newborn lungs. Compared with the fetal PVs and SMCs, PAF-Ah activity in newborn was 40–60% greater. PAF-Ah mRNA expression in newborn vessels was different from the expression by fetal PA. PAF-Ah gene clone activity confirmed deletion of hypoxia-sensitive site. PAFR mRNA expression by the PVs and SMC-PV of the fetus and newborn was greater than by corresponding PAs and SMC-PA. Q-PCR study of PAFR expression by the SMC-PV of both groups was greater than SMC-PA. Fetal SMCs bound more PAF than the newborn SMCs. PAFR antagonist, CV-3988, inhibited PAFR binding and DNA synthesis by the fetal SMCs, but augmented binding and DNA synthesis by newborn cells. We show different PAF–PAFR mediated effects in perinatal lungs, suggesting both transcriptional and translational regulation of PAF-Ah and PAFR expression in the perinatal lamb lungs. These indicate that the downregulation of PAF-mediated effects postnatally protects against persistent pulmonary hypertension of the newborn.